Effects of childhood trauma exposure and cortisol levels on cognitive functioning among breast cancer survivors. (October 2017) - Kamen, Charles; Scheiber, Caroline; Janelsins, Michelle; Jo, Booil; Shen, Hanyang; Palesh, Oxana
Abstract: Cognitive functioning difficultiesin breast cancer patients receiving chemotherapy are common, but not all women experience these impairments. Exposure to childhood trauma may impair cognitive functioning following chemotherapy, and these impairments may be mediated by dysregulation of hypothalamic-pituitary-adrenal (HPA) axis function and cortisol slope. This study evaluated the association between childhood trauma exposure, cortisol, and cognition in a sample of breast cancer survivors. 56 women completed measures of trauma exposure (the Traumatic Events Survey), salivary cortisol, and self-reported cognitive functioning (the Functional Assessment of Cancer Therapy – Cognitive). We examined correlations between childhood trauma exposure and cognitive functioning, then used linear regression to control for factors associated with cognition (age, education, time since chemotherapy, depression, anxiety, and insomnia), and the MacArthur approach to test whether cortisol levels mediated the relationship between trauma and cognitive functioning. 57.1% of the sample had experienced at least one traumatic event in childhood, with 19.6% of the sample witnessing a serious injury, 17.9% experiencing physical abuse, and 14.3% experiencing sexual abuse. Childhood trauma exposure and cognitive functioning were moderately associated (r = −0.29). This association remained even when controlling for other factors associated with cognition; the final model explained 47% of the variance in cognitive functioning. The association between childhood trauma and cognitive functioning was mediated by steeper cortisol slope (partial r = 0.35, p = 0.02). Childhood trauma exposure is associated with self-reported cognitive functioning among breast cancer survivors and is mediated by cortisol dysregulation. Trauma should be considered, among other factors, in programs aiming to address cognition in this population.